PENGENDALIAN KUALITAS PRODUKSI DENGAN MODEL GRAFIK KONTROL P PADA PT. ASERA TIRTA POSIDONIA - Didi Haryono (Universitas Bumigora, 2017)
This study aims to analyze the quality control production with P-control chart model as an effort to suppress the number of defective products and identify factors that cause defects of produced in PT. Asera Tirta Posidonia. This research is a quantitative research with secondary data. The data analysis steps used are check sheet and histogram to present data, P-control chart, using fish bone diagram, and recommendation/ suggestion in quality improvement. This research can be concluded with looking at P-control chart which shows that product quality is the statistical out control. This can be seen in the control chart showing there are points limit out the control and the point is fluctuating and irregular. This is an indication that the process is in a state of uncontrolled or experiencing irregularities that need to be repaired. The results of fishbone diagram analysis can be known that four factors cause defects in the production process is derived from workers, production machine, methods, materials and environment. Therefore, the factors causing defects can be immediately done remedial action in order to avoid greater defects again based on proposed improvement actions that have been stated.